Is quality affordable for community health systems? Costs of integrating quality improvement into close-to-community health programmes in five low-income and middle-income countries - Kumar, Meghan Bruce (BMJ Glob Health, 2019)
INTRODUCTION: Countries aspiring to universal health coverage view close-to-community (CTC) providers as a low-cost means of increasing coverage. However, due to lack of coordination and unreliable funding, the quality of large-scale CTC healthcare provision is highly variable and routine data about service quality are not trustworthy. Quality improvement (QI) approaches are a means of addressing these issues, yet neither the costs nor the budget impact of integrating QI approaches into CTC programme costs have been assessed. METHODS: This paper examines the costs and budget impact of integrating QI into existing CTC health programmes in five countries (Ethiopia, Indonesia, Kenya, Malawi, Mozambique) between 2015 and 2017. The intervention involved: (1) QI team formation; (2) Phased training interspersed with supportive supervision; which resulted in (3) QI teams independently collecting and analysing data to conduct QI interventions. Project costs were collected using an ingredients approach from a health systems perspective. Based on project costs, costs of local adoption of the intervention were modelled under three implementation scenarios. RESULTS: Annualised economic unit costs ranged from $62 in Mozambique to $254 in Ethiopia per CTC provider supervised, driven by the context, type of community health model and the intensity of the intervention. The budget impact of Ministry-led QI for community health is estimated at 0.53% or less of the general government expenditure on health in all countries (and below 0.03% in three of the five countries). CONCLUSION: CTC provision is a key component of healthcare delivery in many settings, so QI has huge potential impact. The impact is difficult to establish conclusively, but as a first step we have provided evidence to assess affordability of QI for community health. Further research is needed to assess whether QI can achieve the level of benefits that would justify the required investment.